Sanksi Tindak Pidana Pada Adat Mendangdangi di Kemukiman Punaga Menurut Hukum Islam - Andri, Andri (Journal of Dual Legal Systems, 2024)
In Article 351 of the Criminal Code, it is stated that minor persecution is punished by law for 2 years and 8 months, persecution with serious injury, punishable for 5 years, if the act results in the death penalty for a maximum of seven years. In the Qur'an, the perpetrators of persecution who are legally and convincingly proven are threatened with the crime of qishash. If the family forgives, then the punishment will be changed to diyat. In the community of Gunung Meriah District, Punaga Settlement, Aceh Singkil Regency, the crime of persecution is subject to sanctions in the form of mendangdangi if the head injury is subject to the sanction of belo pepinangen, one goat, yellow rice, pung tawari, money 21 for ordinary people and 41 for the descendants of the king. Meanwhile, injuries other than the head are subject to the same sanctions as the sanction for injuries to the head but one goat. The results of the study show that the practice of mendangdangi custom is carried out and reconciled at the house of one of the traditional leaders to hold a peace deliberation whether it is reconciled at the police station or according to the mendangdangi custom. Meanwhile, the legal basis set by the Traditional Leader in resolving the crime of persecution in the mendangdangi custom is the Qur'an surah al-Baqarah verse 178 and An-Nahl verse 126. And regarding the view of Islamic law on the practice of the Mendangdangi custom is not contrary to Islamic law, because no evidence has been found, the verse also supports the practice through the mendangdangi custom. [Dalam Pasal 351 KUHP disebutkan bahwa penganiayaan ringan di hukum selama 2 tahun 8 bulan, penganiayaan luka berat, dihukum selama 5 tahun, jika perbuatan tersebut mengakibatkan orang mati dihukum selama-lamanya tujuh tahun. Dalam al-Qur’an bagi pelaku penganiayaan yang terbukti secara sah dan meyakinkan diancam dengan pidana qishash. Bila keluarga memberi maaf, maka hukumannya beralih menjadi diyat. Di masyarakat Kecamatan Gunung Meriah Kemukiman Punaga Kabupaten Aceh Singkil bahwa tindak pidana penganiayaan dikenakan sanksi berupa mendangdangi kalau luka kepala dikenakan sanksi belo pepinangen, satu ekor kambing, nasi kuning, menepung tawari, uang 21 untuk masyarakat biasa dan 41 untuk keturunan raja. Sedangkan luka selain kepala, dikenakan sanksi yang sama seperti sanksi luka di kepala melainkan satu ekor kambing. Hasil penelitian menunjukan praktik adat mendangdangi dilakukan dan didamaikan dirumah salah satu tokoh adat untuk mengadakan musyawarah perdamaian apakah didamaikan dikantor polisi atau menurut adat mendangdangi. Sedangkan dasar hukum yang dipatokkan Tokoh Adat dalam menyelesaikan tindak pidana penganiayaan pada adat mendangdangi adalah al-quran surah al-Baqarah ayat 178 dan An-Nahl ayat 126. dan mengenai pandangan hukum islam terhadap praktik adat mendangdangi tidak bertentangan dengan hukum Islam, dikarenakan tidak ada dalil yang ditemui, dalam ayat juga mendukung atas praktik melalui adat mendangdangi tersebut].